2023
DOI: 10.1021/acs.jpcc.3c04541
|View full text |Cite
|
Sign up to set email alerts
|

C1 Chemistry on Metal Carbide Nanoparticles: Boosting the Conversion of CO2 and CH4

José A. Rodriguez,
Carlos Jimenez-Orozco,
Elizabeth Flórez
et al.

Abstract: The studies described in this Perspective show that transition metal carbide (TMC) nanoparticles can be very useful for the activation of three molecules located at the heart of C 1 chemistry: H 2 , CH 4 , and CO 2 . They also can play a major role in the trapping and conversion of two major greenhouse gases. A combination of experiment and theory has shed light on the physical and chemical properties of these systems, which can be very different from those of bulk carbides. Molecular clusters of these compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…In comparison to pure metals, TMCs are considered as superior potential industrial catalysts due to their higher selectivity, durability, and stability. , It is known that the incorporation of carbon changes the electronic properties and crystal structures of TMCs, while the influence of the number of carbon atoms in active sites on catalytic performance is crucial but not yet being well understood . A few reports have shown that the carbon/metal ratio has a significant impact on the reactivity of niobium carbide (Nb x C y ), while the majority of reports focus on molybdenum carbide (Mo x C y ) .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to pure metals, TMCs are considered as superior potential industrial catalysts due to their higher selectivity, durability, and stability. , It is known that the incorporation of carbon changes the electronic properties and crystal structures of TMCs, while the influence of the number of carbon atoms in active sites on catalytic performance is crucial but not yet being well understood . A few reports have shown that the carbon/metal ratio has a significant impact on the reactivity of niobium carbide (Nb x C y ), while the majority of reports focus on molybdenum carbide (Mo x C y ) .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, nano-TMCs are able to expose active sites more efficiently in the catalytic reaction, and secondly, nano-TMCs are cut from bulk TMCs and have unique metal/C ratios and structures different from bulk TMCs, as well as corner or edge atoms that are active for C-O bond breaking and activation. [85] In view of this, Zhang et al successfully obtained 2D 𝛽-Mo 2 C nanorods with abundantly stacked nanopores by carburizing the hydrothermally synthesized MoO 3 nanorods as precursors (Figure 12a,b). [86] The specific surface area [86] Copyright 2020, Elsevier.…”
Section: Construction Of Tmcs With Specific Nano-micro Morphologymentioning
confidence: 99%
“…Another interesting research topic of TMCs pertains to the finding of Ti 8 C 12 as a class of metallocarbohedrenes (Met-Cars) with a common stoichiometry of M 8 C 12 (M = Ti, V, Cr, Zr, Hf, Nb, Mo, etc. ), which was repeatedly observed during dehydrogenation reactions of hydrocarbons with metal atoms/ions and small clusters in the plasma atmosphere. Met-Cars are attractive in the application potentials for hydrogen storage and catalytic reactions including the novel C1 chemistry. Recently, by downstream reactions of pure Co n – and Ni n – clusters with acetylene, stable M 12 C 12 – (M = Fe, Co, Ni) clusters have also been identified. , However, it is still unclear if super magic TMCs are limited to M 8 C 12 and M 12 C 12 . Further insights into the chemical reactivity, the bonding nature, and the structure–property relationship still need to be further explored. , Also, it is anticipated that stable TMCs can be tailored with tunable structures and properties at atomic precision as well as novel quantum size effects and superatomic features. …”
Section: Introductionmentioning
confidence: 99%